2004
DOI: 10.1103/physreva.69.032708
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of absoluteK-shell ionization cross sections andL-shell x-ray production cross sections of Ge by electron impact

Abstract: Results from measurements of absolute K-shell ionization cross sections and L␣ x-ray production cross sections of Ge by impact of electrons with kinetic energies ranging from the ionization threshold up to 40 keV are presented. The cross sections were obtained by measuring K␣ and L␣ x-ray intensities emitted from ultrathin Ge films deposited onto self-supporting carbon backing films. Recorded x-ray intensities were converted to absolute cross sections by using estimated values of the sample thicknesses, the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…For the experimental data of L-shell X-ray production cross sections, from the recently published papers we noticed that for higher-Z elements, for example, W (Z = 74), Pt (Z = 78), Au (Z = 79) [10] Au (Z = 79) [8] and Pb (Z = 82) [16], the DWBA [4][5][6] and PWBA-C-Ex theories [2,3] can describe very well the experimental L a [10] and L a , L b [8] X-ray production cross sections. However, for lower-Z elements, for example, Ga (Z = 31), As (Z = 33) [9] and Ag (Z = 47) [8], the predictions of the DWBA theory [4][5][6] and the PWBA-C-Ex theory [2,3] are similar [9] and in general $10-25% larger than the experimental data [8,9], but except for Ge (Z = 32) element where the predictions of the DWBA theory [4][5][6] were slightly smaller than the experimental data [11]. Therefore, in general, it seems that the theoretical models recently developed can better describe the K-shell experimental data for medium-Z elements than for lower-Z and higher-Z elements, and better describe the L-shell experimental data for higher-Z elements than for lower-Z elements.…”
Section: Introductionmentioning
confidence: 47%
See 2 more Smart Citations
“…For the experimental data of L-shell X-ray production cross sections, from the recently published papers we noticed that for higher-Z elements, for example, W (Z = 74), Pt (Z = 78), Au (Z = 79) [10] Au (Z = 79) [8] and Pb (Z = 82) [16], the DWBA [4][5][6] and PWBA-C-Ex theories [2,3] can describe very well the experimental L a [10] and L a , L b [8] X-ray production cross sections. However, for lower-Z elements, for example, Ga (Z = 31), As (Z = 33) [9] and Ag (Z = 47) [8], the predictions of the DWBA theory [4][5][6] and the PWBA-C-Ex theory [2,3] are similar [9] and in general $10-25% larger than the experimental data [8,9], but except for Ge (Z = 32) element where the predictions of the DWBA theory [4][5][6] were slightly smaller than the experimental data [11]. Therefore, in general, it seems that the theoretical models recently developed can better describe the K-shell experimental data for medium-Z elements than for lower-Z and higher-Z elements, and better describe the L-shell experimental data for higher-Z elements than for lower-Z elements.…”
Section: Introductionmentioning
confidence: 47%
“…The detection efficiency calibration of the Si(Li) detector was performed by using 241 Am standard radioactive source in combination with the bremsstrahlung spectrum of carbon thick-target by electron impact [8,11,24]. The shape of the efficiency calibration curve was determined from the ratio of experimental and theoretical bremsstrahlung spectra of carbon thick-target by electron impact, and the absolute values of the efficiency calibration were obtained by using the 241 Am standard radioactive source.…”
Section: Experiments and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, ionization cross sections can be converted into x-ray emission cross sections using atomic relaxation parameters. Previous studies have shown satisfactory agreement between DWBA calculations and several experiments [5,[7][8][9][10]. The emphasis was on K-shell ionization of atoms with intermediate or large atomic number Z, and L-shell ionization of intermediate Z.…”
Section: Introductionmentioning
confidence: 86%
“…X‐ray production cross sections were obtained by recording x‐ray intensities emitted from ultrathin films of the considered elements (Au, Pb, Bi, and U) deposited onto self‐supporting thin C backing films, using electron microprobes . To ensure that the M x‐ray lines were satisfactorily resolved, wavelength‐dispersive spectrometers (WDSs) were used.…”
Section: Methodsmentioning
confidence: 99%